Filmar la ciudad - García-Defez, Olga (Comunicación y Medios, 2023)
Nancy Berthier, Carlos Belmonte, Álvaro A. Fernández. (coords.)(2021). Filmar la ciudad. Guadalajara: Editorial Universidad de Guadalajara. 336 páginas. ISBN: 978-607-571-060-0